I'm asked to solve the equation dy/dx = (2x+y-1)/ (4x-2y +1) using substituition of x = X+1 , y = Y-1 , the ans given is ( (x-y-2)^2) (x^2 -2x -y^2 -2y) = c , anyone can point out where's my mistake ?Attachment 35344

Printable View

- Feb 16th 2016, 06:58 AMxl5899dy/dx = (2x+y-1)/ (4x-2y +1)
I'm asked to solve the equation dy/dx = (2x+y-1)/ (4x-2y +1) using substituition of x = X+1 , y = Y-1 , the ans given is ( (x-y-2)^2) (x^2 -2x -y^2 -2y) = c , anyone can point out where's my mistake ?Attachment 35344